Numerical study on effects of hydrogen direct injection on hydrogen mixture distribution, combustion and emissions of a gasoline/hydrogen SI engine under lean burn condition. (13th January 2020) - Yu, Xiumin; Li, Guanting; Dong, Wei; Shang, Zhen; Guo, Zezhou; Li, Yinan; Li, Decheng; Zhao, Zhe
Abstract: A numerical study on effects of hydrogen direct injection on hydrogen mixture distribution, combustion and emissions was presented for a gasoline/hydrogen SI engine. Under lean burn conditions, five different direct hydrogen injection timings were applied at low speeds and low loads on SI engines with direct hydrogen injection (HDI) and gasoline port injection. The results were showed as following: firstly, with the increase of hydrogen direct injection timing, the hydrogen concentration near the sparking plug first increases and then decreases, reaching the highest when hydrogen direct injection timing is 120°CA BTDC: Secondly, hydrogen can speed up the combustion rate. The main factor affecting the combustion rate and efficiency is the hydrogen concentration near the sparking plug: Thirdly, in comparing with gasoline, the NOX emissions with hydrogen addition increase by an average of 115%. For different hydrogen direct injection timings, the NOX emissions of 120°CA BTDC is the highest, which is 29.9% higher than the 75°CA BTDC. The hydrogen addition make the NOX emissions increase in two ways. On the one hand, the average temperature with hydrogen addition is higher. On the other hand, the temperature with hydrogen addition is not homogeneous, which makes the peak of temperature much higher. In a word, the main factor of NOX emissions is the size of high temperature zone in the cylinder: Finally, because the combustion is more complete, in comparing with gasoline, hydrogen addition can reduce the CO and HC emissions by 32.2% and 80.4% respectively. Since a more homogeneous hydrogen mixture distribution can influence a lager zone in the cylinder and reduce the wall quenching distance, these emissions decrease with the increase of hydrogen direct injection timing. The CO and HC emissions of 135°CA BTDC decrease by 41.5% and 71.4%, respectively, compared to 75°CA BTDC. Highlights: Hydrogen mixture distribution affects a lot on combustion and emissions. Hydrogen direct injection timing can control the hydrogen mixture distribution. There is a best hydrogen direct injection timing for a gasoline/hydrogen SI engine. The hydrogen concentration near the sparking plug influences the combustion a lot. It deeply analyzes that how hydrogen addition makes NOX emissions increase.